Colloidal size spectra, composition and estuarine mixing behavior of DOM in river and estuarine waters of the northern Gulf of Mexico. (15th May 2016) - Zhou, Zhengzhen; Stolpe, Björn; Guo, Laodong; Shiller, Alan M.
Abstract: Flow field-flow fractionation (FlFFF) coupled on-line with UV absorbance and fluorescence detectors was used to examine the colloidal composition and size distribution of optically active dissolved organic matter (DOM) in the lower Mississippi River (MR), the East Pearl River (EPR), the St. Louis Bay (SLB) estuary, and coastal waters of the northern Gulf of Mexico. In addition to field studies, laboratory mixing experiments using river and seawater end-members were carried out to study the processes controlling the estuarine mixing behavior and size partitioning of colloids with different sizes and composition. The colloidal size spectra of chromophoric DOM and humic-like DOM showed one dominant peak in the 0.5–4 nm size range, representing >75% of the total FlFFF-recoverable colloids. In contrast, protein-like DOM showed a bi-modal distribution with peaks at 0.5–4 nm and 4–8 nm, as well as a major portion (from ∼41% in the EPR to ∼72% in the Mississippi Bight) partitioned to the >20 nm size fraction. Bulk DOM was lower in abundance and molecular-weight in the MR compared with the EPR, while the proportion of colloidal protein-like DOM in the >20 nm size range was slightly larger in the MR compared with the EPR. These features are consistent with differences in land use, hydrological conditions, and water residence time between the two river basins, with more autochthonous DOM in MR waters. In the SLB estuary, different DOM components demonstrated different mixing behaviors. The abundance of colloidal chromophoric DOM decreased with increasing salinity and showed evident removal during estuarine mixing even though the bulk DOM appeared to be conservative. In contrast, colloidal humic-like DOM behaved conservatively inside SLB and during laboratory mixing experiments. The ratio of colloidal protein-like to humic-like DOM generally increased with increasing salinity, consistent with increasing autochthonous protein-like DOM and removal of terrestrially-derived humic-like DOM in estuarine and coastal waters. Similar mixing behavior for the bulk DOM and colloids was observed in short-term laboratory mixing experiments, suggesting that physicochemical processes are the major controlling factor for colloidal removal in the estuary. For the first time, this study showed direct evidence of contrasting estuarine mixing behavior for different size fractions of optically active colloidal DOM.